Quintiliano, Agustín y Fray Luis de Granada ante la doctrina de la alegoría - López Muñoz, Manuel (Florentia iliberritana: Revista de estudios de antigüedad clásica, 1992)
The author analizes the historical development of the rhetorical theories concerning allegory, either as a production facility given to the artifex during the elocuno or as an exegetic principle for the theologian. The allegoria then becomes a two-faced reality, often studied from the point of view of the sender of the message or from the one of the receiver, but not from both. As a preliminary basis for ulterior discussions, the author compares the theories formulated by Quintilian -this is, the rhetorical approach from the domain of the sender-, Saint Augustine -theorist of the decodification of the message contained in the Holy Bible-and fray Luis de Granada, who shares both approaches to the theory of allegory and includes them in different books of his Ecclesiasticae Rhetoricae siue de ranone concionandi libri, probably one of the most influential Renaissance catholic treatises on preaching.